2016
DOI: 10.1002/adfm.201602207
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity and Uncertainty in Intrafibrillar Mineralization of Collagen

Abstract: Biomineralization in vertebrates is a ubiquitous and tightly regulated process which creates hierarchical structures for the skeleton. Because of the lack of understanding and applicability of cell‐based or biological systems to achieve intrafibrillar mineralization, scientists adopted various in vitro methods to elucidate the mechanism of intrafibrillar mineralization. In this article, biomimetic intrafibrillar mineralization of collagen in its wide ramifications is reviewed. It is intriguing how prevailing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 174 publications
2
80
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] Today, there is mounting evidence that in animal bones and teeth, ACP is a precursor to apatites (or an important component of the complex structures), [15][16][17][18][19][20][21][22] and liquid precursors may also play a role in CaP biomineralization. [23][24][25] ions were shown to be present within an "acidic" ACP, which is thought to be essential for CaP biomineralization. 21 Generally, the term "acidic" ACP implies that HPO4 2-ions are present in the material, yielding Ca/P atomic ratios between ~1.0-1.5 even though it is obtained at near-neutral, slightly basic pH values.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Today, there is mounting evidence that in animal bones and teeth, ACP is a precursor to apatites (or an important component of the complex structures), [15][16][17][18][19][20][21][22] and liquid precursors may also play a role in CaP biomineralization. [23][24][25] ions were shown to be present within an "acidic" ACP, which is thought to be essential for CaP biomineralization. 21 Generally, the term "acidic" ACP implies that HPO4 2-ions are present in the material, yielding Ca/P atomic ratios between ~1.0-1.5 even though it is obtained at near-neutral, slightly basic pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Biomineralization is a widespread phenomenon in nature leading to the formation of hierarchically structured minerals by living organisms [31][32][33] . It has been revealed that biomolecules, particularly the stereochemical side chains within them, can guide the nucleation and growth of mineral crystals [34][35][36][37] . As a well-known example in biomineralization, the eggshell has attracted much attention, because its calcified crystallization ( Fig.…”
mentioning
confidence: 99%
“…Other polymer additives include poly(glutamic acid) (pGlu), poly(amidoamine) dendrimers, poly(acrylic acid) (PAA), typically used in combination with poly(vinylphosphonic acid) (PVPA), sodium trimethaphosphate (STMP), poly(glutamic acid), or phosphorylated collagen . The only example of a cationic polymer able to induce intrafibrillar mineralization of collagen is the one of poly(allylamine) hydrochloride (PAH) …”
Section: Biomineralization‐inspired Materialsmentioning
confidence: 99%
“…For example, collagen substrates have been used as reconstituted fibrils or sponges (sometimes called membranes) from acid‐ or enzyme‐extracted collagen (that can be prepared in‐house or purchased). They can originate from rat‐tail tendon, bovine or equine tendon, or bovine skin . Substrates have also been prepared directly from biological tissue, such as turkey tendon, demineralized sections from mouse periodontium, and bone from manatee, or fish origin, as well as demineralized dentin from mouse, or human origin …”
Section: Biomineralization‐inspired Materialsmentioning
confidence: 99%
See 1 more Smart Citation